EKSISTENSI AHLI WARIS PENGGANTI DALAM HUKUM ADAT KAMPAR KECAMATAN BANGKINANG PERSPEKTIF KOMPILASI HUKUM ISLAM - Desma Royana; Sofia Hardani; Mohd. Yunus (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2022)
Indigenous Kampar communities, such as those in Bangkinang Sub-district, basically adhere to the principle of matrilineal kinship, therefore each individual draws their lineage FROM the mother's side. The majority of the Kampar indigenous people of Bangkinang sub-district are Muslims. They have the principle of "Adat Bersendi Syarak, Syarak Bersendi Kitabullah", it can be seen that the law that applies to adat Kampar is customary law that cannot be separated from Islamic teachings. can be seen in the practice of inheritance of grandchildren as a substitute for their parents who prioritize benefit and justice. The formulation of this THESIS problem is how to solve the replacement heirs in the Kampar district community in Bangkinang District. How is the existence of substitute heirs according to the Compilation of Islamic Law and Kampar Customs in Bangkinang District. What are the values of justice and benefit when giving inheritance to grandchildren whose parents died before them. This research is qualitative. The first step in this research is field observations by observing the implementation of the law on the inheritance of grandchildren whose parents died earlier than their in the Bangkinang District community. This research uses Rawls' theory of justice, in analyzing the data of this research. This research shows that the spirit of implementing customary law in Kampar on Islamic law, especially in the field of inheritance, is the spirit of benefit and justice. The interesting thing about this research is that the granddaughter who replaces the position of her parents who died first will definitely get her share even though she is legally veiled and is not entitled to inherit property. However, the Kampar indigenous people of Bangkinang Sub-district continue to give grandchildren whose parents died from them first.